'No‐one actually goes to a shop and buys them do they?': attitudes and behaviours regarding illicit tobacco in a multiply disadvantaged community in England. (9th October 2013) - Stead, Martine; Jones, Laura; Docherty, Graeme; Gough, Brendan; Antoniak, Marilyn; McNeill, Ann
Abstract Aims To explore attitudes towards, and experience of, illicit tobacco usage in a disadvantaged community against a backdrop of austerity and declining national trends in illicit tobacco use. Design Qualitative study using 10 focus groups. Setting Multiply disadvantaged community in Nottingham, United Kingdom. Participants Fifty‐eight smokers, ex‐ and non‐smokers aged 15–60 years. Measurements Focus group topic guides. Findings There was high awareness and use of illegal tobacco sources, with 'fag houses' (individuals selling cigarettes from their own homes) being particularly widespread. Rather than being regarded as marginal behaviour, buying illicit tobacco was perceived as commonplace, even where products were known to be counterfeit. Smokers' willingness to smoke inferior 'nasty' counterfeit products may be testament to their need for cheap nicotine. Illicit tobacco was seen to be of mutual benefit to both user (because of its low cost) and seller (because it provided income and support for the local economy). Illicit tobacco sellers were generally condoned, in contrast with the government, which was blamed for unfair tobacco taxation, attitudes possibly heightened by the recession. Easy access to illicit tobacco was seen to facilitate and sustain smoking, with the main concern being around underage smokers who were perceived to be able to buy cheap cigarettes without challenge. Conclusions National strategies to reduce illicit tobacco may have limited impact in communities during a recession and where illicit trade is part of the local culture and economy. There may be potential to influence illicit tobacco use by building on the ambivalence and unease expressed around selling to children.